2002
DOI: 10.1038/sj.bjc.6600296
|View full text |Cite
|
Sign up to set email alerts
|

A novel combretastatin A-4 derivative, AC7700, strongly stanches tumour blood flow and inhibits growth of tumours developing in various tissues and organs

Abstract: In a previous study, we used subcutaneous LY80 tumours (a subline of Yoshida sarcoma), Sato lung carcinoma, and methylcholanthrene-induced primary tumours, to demonstrate that a novel water-soluble combretastatin A-4 derivative, AC7700, abruptly and irreversibly stopped tumour blood flow. As a result of this interrupted supply of nutrients, extensive necrosis was induced within the tumour. In the present study, we investigated whether AC7700 acts in the same way against solid tumours growing in the liver, stom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 33 publications
(34 reference statements)
1
48
0
Order By: Relevance
“…AC7700 works both in rapidly proliferating transplanted tumours and in relatively slowly proliferating primary tumours induced by chemical carcinogens (Hori et al, 2001). Recently, such effectiveness was confirmed in tumours growing within internal organs, including the liver, kidney, and stomach, as well as in metastatic lymph nodes and small 2.5-mm-diameter foci (Hori et al, 2002), which suggests that these effects might be obtained in all types of solid tumours. Since early 2002, AC7700 has been undergoing clinical trials in Europe and the US under the new code name AVE8062.…”
mentioning
confidence: 90%
“…AC7700 works both in rapidly proliferating transplanted tumours and in relatively slowly proliferating primary tumours induced by chemical carcinogens (Hori et al, 2001). Recently, such effectiveness was confirmed in tumours growing within internal organs, including the liver, kidney, and stomach, as well as in metastatic lymph nodes and small 2.5-mm-diameter foci (Hori et al, 2002), which suggests that these effects might be obtained in all types of solid tumours. Since early 2002, AC7700 has been undergoing clinical trials in Europe and the US under the new code name AVE8062.…”
mentioning
confidence: 90%
“…Preclinical studies have shown rapid and irreversible vascular shutdown in various different orthotopic tumour models. Complete stasis of blood flow was observed after 30 min, whereas blood flow in normal tissues was compromised but returned to pretreatment levels within 24 h. Tumour cell proliferation in different models was suppressed after drug infusion (Hori et al, 2002). So far only one phase-I single-agent study has been published in which nine patients received 48 infusions of AVE8062 (Table 1) (Tolcher et al, 2003).…”
Section: Ave8062mentioning
confidence: 99%
“…8,9 CA4P and other VDAs are highly selective for rodent and human tumors where they cause significantly greater vascular damage compared with normal tissues. [8][9][10][11][12] The mechanisms through which VDAs elicit their anti-tumor activity are conceptually different from those of classic chemotherapeutic agents that directly target the tumor cell component and kill cells by apoptosis or related mechanisms. 13 Although the precise molecular pathways that drive tumor vascular collapse are not yet fully understood, in vitro analyses have shown that VDAs act through binding to tubulin resulting in microtubule depolymerization, triggering morphological changes in endothelial cells that include increased blebbing and contraction, contributing to the disruption of cell-to-cell junctions and increased permeability.…”
mentioning
confidence: 99%